ANALYSIS OF THE FINANCIAL POSITION OF ENTERPRISES IN PRIVATIZATION IN THE AGRICULTURAL SECTOR IN SERBIA - Vukadinović, Predrag; Vujović, Slavoljub; Vojnović, Boško (Economics of Agriculture, 2018)
Privatization as a phase of the transitional process also included agriculture. The most attractive enterprises in agriculture, primarily in the food industry, were privatized in the first wave, while the process of privatization of other less attractive companies was slowed down and implemented mainly by the auction model. The remaining companies waiting for the privatization process are not attractive and there are problems that are expressed through poor financial position and relatively low potential. An exception is made by PKB Corporation, which has a potential and relatively stable market, making this company an acceptable option for investors. The financial position of the companies that are ready for privatization at this moment and which is one of the factors of negative influence on the decision of the investor was analyzed using the Altman Z-score model, the Kralicek Quick test and the balanced growth model. All tests have shown that the analyzed companies are in a bad financial position and that the future investor will have to invest significant funds in financial consolidation, balancing cash flows and investment in order to ensure adequate development and efficient business.